Systemic reprogramming of endothelial cell signaling in metastasis and Cachexia - Preuss, Stephanie; Grieshober, Denise; Augustin, Hellmut (Physiology, 2023)
Proliferating cancer cells secrete a multitude of factors impacting metabolism, interorgan communication, and tumor progression. The distribution of tumor-derived factors to distant organs occurs via the circulation, which provides an extensive reactive surface lined by endothelial cells. Primary tumor-derived proteins impact cancer progression by modulating endothelial cell activation at the (pre-)metastatic niche, which affects tumor cell dissemination as well as the outgrowth of seeded metastatic cells into overt tumors. In addition, new insight indicates that endothelial cell signaling contributes to metabolic symptoms of cancer, including cancer-associated cachexia, opening a new field of vascular metabolism research. This review addresses how tumor-derived factors systemically affect endothelial cell signaling and activation and impact distant organs as well as tumor progression.